International dating how Filipinas in Filipina-Westerner relationships use social networking sites in relationship negotiations - Alvarez, Lourdes Christine T. 1997- (2018)
This thesis examines how Filipinas engaged in international dating use SNS to negotiate their gender when going through the relationship building process with Westerners. Internation dating traces its origins from a phenomenon known as mail-order relationships; the researcher has found various literature that looked into the mail-order phenomenon, but little to no studies have focused on international dating specifically at the advent of different SNS. Moreover, pervious literatures tend to portray the women in these relationships as oppressed entities incapable of choice. In this thesis, however, the focus was put on the women, specifically Filipinas in Filipina-Westerner relationships built through international dating, in order to understand how they use SNS to their advantage through negotiating their gender withing the relationships. 15 Filipinas engaged in international dating were asked to participate in focus interviews that aimed to explicate their use of SNS in relationship building and then later, make sense of their gender negotiations vis-a-vis relationship building within SNS. Findings of the study show that Filipinas use SNS to their advantage by taking control of their relationships. overall, the study points to a more empowered use of SNS by the Filipinas by way of negotiating their gender within international dating."